Conceptual design of cryostat for cryo-cooled 37 elements phased array radar system for space surveillance. Issue 1 (1st May 2022) - Froehlich, A.; Barbri, H.; Ben Bekhti-Winkel, N.; Grenz, O.; Koenig, F.; Naumann, L.; Putselyk, S.; Schneider, M.; Tiesing, M.; Wirths, T.
Abstract: The amount of space debris orbiting the earth is increasing. More than 700 000 objects with critical sizes of more than 1 cm have the potential to cause severe damage to space-based infrastructure. Improving the sensitivity of next generation space surveillance RADARs is necessary for the ability to detect space debris with sizes down to 1 cm. For a successful detection, a key parameter is the signal-to-noise ratio (SNR). Therefore the Fraunhofer Institute for High Frequency Physics and Radar Technique (FHR) analyses cryogenic cooled receivers for space surveillance RADAR systems. In addition to electrical frequency, the requirements of a mechanical design for a large cryo-cooled phased array receiver is challenging. In previous papers, an interim stage 7-element cryogenic receiver with cold antennas was mentioned as well as first studies of a scalable RF unit cell. The present paper shows the prototype and first results of a 37 – element phased array receiver, based on simulations. The design of a cryogenic phased array requires thermal and mechanical simulations in consideration with the modular design concept including the scalable unit cell. Referring to the German Space Surveillance Tracking RADAR (GESTRA) operating in L-band leads to the large receiver size due to the free-air wavelength of 23 cm. This paper presents our approach in the design of a 37 cryogenic phased array. It presents the simulation with focus on thermal transitions, heat loads and mechanical stress.